2019
DOI: 10.1038/s41598-019-46096-w
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of a novel strain of dolphin morbillivirus (DMV) in stranded cetaceans in the Mediterranean Sea

Abstract: Dolphin morbillivirus (DMV) has been responsible for several outbreaks of systemic infection and has resulted in cetacean strandings in the Mediterranean. In August-October 2016, seven striped dolphins ( Stenella coeruleoalba ) stranded on the Sicilian coastline (Italy) tested positive for DMV. Tissue samples from brain, lung, pulmonary lymph nodes, heart, spleen, liver, stomach, intestine, kidneys and urinary bladder, as well as blowhole swabs, were collected during necropsy for molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
(81 reference statements)
3
13
0
Order By: Relevance
“…Recent phylogenic and phylogeographic analysis [ 10 ] on 16 strains that circulated in the last 30 years in the Mediterranean confirmed a general well-conserved homology among the strains, with an overall sequence identity >98%. A novel lineage of Atlantic origin, named NE-Atlantic strain because first detected in animals found stranded along the coasts of Galicia and Portugal in 2011–2013, started to replace the Mediterranean strain by late 2015 in Italian waters [ 10 , 11 , 12 ]. The first description of the NE-Atlantic strain in the Mediterranean basin refers to a sperm whale ( Physeter macrocephalus Linnaeus, 1758) found stranded on the coast of Vasto (CH) in 2014 [ 10 ] during a mass stranding episode that involved seven individuals [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent phylogenic and phylogeographic analysis [ 10 ] on 16 strains that circulated in the last 30 years in the Mediterranean confirmed a general well-conserved homology among the strains, with an overall sequence identity >98%. A novel lineage of Atlantic origin, named NE-Atlantic strain because first detected in animals found stranded along the coasts of Galicia and Portugal in 2011–2013, started to replace the Mediterranean strain by late 2015 in Italian waters [ 10 , 11 , 12 ]. The first description of the NE-Atlantic strain in the Mediterranean basin refers to a sperm whale ( Physeter macrocephalus Linnaeus, 1758) found stranded on the coast of Vasto (CH) in 2014 [ 10 ] during a mass stranding episode that involved seven individuals [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies on DMV sequences circulating in the Mediterranean basin in the last 30 years show that the strain is generally well conserved [ 9 , 10 ]. In the last 6 years, however, the DMV Mediterranean strain has been substituted by a new variant called DMV northeast (NE)-Atlantic strain originating from the coasts of Galicia and Portugal [ 10 , 11 , 12 ]. No difference in virulence and disease severity between the two strains has been confirmed to date [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of shared habitat and foraging resources between striped and common dolphins would also have an effect on potential exposure to diseases, such as the cetacean or dolphin morbillivirus epizootics that have caused high mortality in odontocetes in Europe, the USA, and Australia (Van Bressem, Van Waerebeek, Jepson, et al, 2001; Van Bressem et al, 2014) and have affected striped dolphins in the Mediterranean (Aguilar & Raga, 1993; Raga et al, 2008) and common dolphins in the Black Sea since the 1990s (Birkun et al, 1999). Novel morbillivirus outbreaks are also being reported to affect striped dolphins in recent years (Mira et al, 2019; Pautasso et al, 2019). It has recently been reported that such cetacean morbillivirus has an increased tendency to cross ‘interspecies barriers’ (Jo, Osterhaus, & Ludlow, 2018), while having an immunosuppressive effect on dolphins becoming predisposed to other infections as well (Keck et al, 2010).…”
Section: Threatsmentioning
confidence: 99%
“…[2][3][4][5] In fact, as outbreaks caused by CeMV in cetaceans from both hemispheres show, the five, hitherto recognized viral strains (termed as CeMV-1 to -5) display a high propensity for multi-host transmission and trans-oceanic spread. 6,7 CeMV infections were reported also in mammals other than cetaceans, including species with mixed aquatic-terrestrial ecology such as the common seal (Phoca vitulina), 8 the Eurasian otter (Lutra lutra), 9 and the endangered Mediterranean monk seal (Monachus monachus). 10 The CeMV host range expansion mirrors the pattern observed for canine distemper virus (CDV) and phocine distemper virus (PDV), two other morbilliviruses infecting aquatic mammals that caused outbreaks among Lake Bajkal seals (Pusa siberica), Caspian seals (Pusa caspica), and North Sea common seals.…”
Section: Introductionmentioning
confidence: 99%
“…The tendency of CeMV to cross interspecies barriers was documented in recent years, showing a progressive widening of the host range and geographical distribution 2–5 . In fact, as outbreaks caused by CeMV in cetaceans from both hemispheres show, the five, hitherto recognized viral strains (termed as CeMV‐1 to ‐5) display a high propensity for multi‐host transmission and trans‐oceanic spread 6,7 . CeMV infections were reported also in mammals other than cetaceans, including species with mixed aquatic‐terrestrial ecology such as the common seal ( Phoca vitulina ), 8 the Eurasian otter ( Lutra lutra ), 9 and the endangered Mediterranean monk seal ( Monachus monachus ) 10 .…”
Section: Introductionmentioning
confidence: 99%